Identifying risk and protective factors, including culture and identity, for methamphetamine use in Aboriginal and Torres Strait Islander communities: Relevance of the 'communities that care' model. (December 2020) - Reilly, Rachel; Gendera, Sandra; Treloar, Carla; Roe, Yvette; Conigrave, Kate; Azzopardi, Peter; Ward, James
Abstract: Background and Aims: There is a need for more evidence to guide efforts to address harmful methamphetamine use amongst young Aboriginal and Torres Strait Islander Australians. 'Communities that Care' (CTC) is an evidence-based process developed to prevent alcohol and other drug-related harm but its suitability for use in Aboriginal contexts has not been established. This study sought to explore whether risk and protective factors for methamphetamine use, as described by Aboriginal stakeholders, align with the CTC risk and protective factor framework. Method: Focus groups and individual interviews were conducted in Aboriginal communities nationally. Data were analysed thematically using the CTC framework as a deductive coding framework. Additional themes were captured and summarised. Results: Participants were 147 (80% Aboriginal; 44% female) key stakeholders aged between 16 and 69 (median=40), recruited via organisational and community networks in each site. Relevant factors were identified in all four CTC domains: community, family, school, peer/individual. However, these four domains did not capture issues of central importance to Aboriginal people. These were summarised as an additional domain, 'Culture and Identity.' Conclusions: Given that the Communities that Care risk and protective framework did not sufficiently capture issues of central importance to Aboriginal people, there is a need for different, community-informed models that reflect the unique determinants of use in this context. Highlights: Methamphetamine use is of deep concern in Aboriginal communities. A deep understanding of risk and protective factors is needed to prevent harm. Many risk and protective factors overlap with mainstream settings but some do not. Culturally informed prevention systems need to include culturally relevant factors.